Epidemiology Study of Contusion Eye - Janicijevic Petrovic, Mirjana Andreja; Sarenac Vulovic, Tatjana; Janicijevic, Katarina; Petrovic, Marko (PONS - medicinski časopis, 2014)
AimAim of article was to show analysis of increase/decrease number of various close contusion of eye between hospital and ambulance patients with epidemiology characteristics. Method Of 444 patients with traumatic ocular injuries (hematoma palpebral, suffusion conjunctiva, erosion corneal, hyphema, iridodialisis, cataract/subluxatio of lens, haemorrhagiae chorioretinal and trauma orbit/optic nerve, who were referred by ophthalmologists from Clinical Centre of Kragujevac, evaluated and included in retrospective study from 2007 to 2012. Epidemiological characteristics included: sex, age, time (calendar), location of professional trauma, address (urban, rural) and treatments of injury (number of hospital and ambulance). Statistical analysis was done with SPSS program, version 20.00 (Chi-square test, Kruskal-Wallis test; p-value include the exact value unless, it is less than 0.01). Results The total number of patients with contusion was 444 which 197 (44.37%) were treated in hospital and 247 (55.63%) by ambulance. Relationship of hospitalized and outpatients, the contusion injuries in favor of first only in 2007, 51 (56.66%), and increased outpatient injury is higher in all of remaining 2008 - 2012, except in 2010 where ratio of hospitalized/ambulance was equivalent 32 (32.07%). Conclusion The most of injuries were 342 (77.03%) men, aged 20-50 years – 166 (37.39%), in autumn months from September to December – 214 (48.20%), with sport activities – 166 (37.39%) and in urban areas – 230 (51.80). The number of hospital is declining, and number is growing ambulance is changing slightly, but total number of violations evidently is declining by 6 years.